A Rare Case of Gastric Metastasis in Ewing’s Sarcoma of the Femur - Krishna Amulya Koti; Selvamani Backianathan; Patricia Sebastian; Leni G. Matthew; Mithun Raam; Dipti Masih (Case Reports in Oncological Medicine)
The stomach is a very unusual site of metastasis. Published reports on metastatic lesion in the stomach is generally limited to single case reports and case series. Gastric metastasis in an Ewing’s sarcoma is extremely rare and has been reported in English literature but once to our knowledge. We present a case report of Ewing’s sarcoma of the right proximal femur metastasizing to the stomach. A young female treated for Ewing’s sarcoma of the femur in 2012 presented with gastric metastasis after four years of disease-free interval. She was treated with irinotecan-based chemotherapy followed by total gastrectomy with esophagojejunal anastomosis and radiation therapy. At one-year follow-up, she was disease free.